Advanced control technique for the DC-DC multilevel converter - Lye, Weng Kuan (Nanyang Technological University, 2020)
The most advanced power converter topology for high voltage direct current (HVDC) transmission is the Modular Multilevel Converter (MMC). MMC are converters that are made up of cascaded connection of many sub-modules or cells usually made of half-bridges that stacked up to make an MMC. IGBT and MOSFET technology are commonly used to build the sub-modules of MMC, which contribute to the reduction of power losses and the converter size. With the capability of their high-frequency switching range, they significantly increase the efficiency of the converters. However, the dramatic power fluctuation in the HVDC will not be mitigated by the traditional power system operation whose response time is relatively long. There are many multiphase multilevel converter topologies, e.g., the CHB converter, the Neutral Point Clamped (NPC) converter, Flying Capacitor (FC) converter, and other derivatives. Among the traditional ones, CHB converters can obtain a high level of modularity than other multiphase multilevel converters and require fewer capacitors and diodes. Thus, the Cascaded Half-bridge (CHB) multilevel converter topology will be used in the report to understand the fundamentals and benefits of the control methods mentioned later on. Moreover, it will also be the remedy to the power fluctuation issue by producing output voltage steps of more than 3 levels, resulting in a higher voltage, power rate, and smoother output, unlike the ordinary multiphase inverters. This report presents two predictive model control (MPC) method for different configurations of DC-AC and DC-DC converter. Before employing and comparing the proposed control methods, studies on the different configurations with being elaborated to understand the advantages and disadvantages of them. Then, the comparison between the conventional PWM technique, FCS-MPC, and FF-MPC algorithms was compiled through MATLAB Simulink. With the simulation, there would be a concrete conclusion and an overview of the merits and drawbacks of each control method proposed. The feasibility and functionality of the FF-MPC method are assessed via simulation and hardware based on the compiled MATLAB codes. Lastly, in order to obtain a dependable suggestion for future work, ideas and concepts would be shared from the findings of this Final Year Project.